The Relationship of Study Habits and VARK Preferences to the Academic Performance of Second Year Education Students - Simon, Estrella O.; Domalaon, Jev C.; Dunghit, Jean C.; Antiporda, Donna P.; Liquigan, Patricia; Rivera , Ruth (International Journal of Psychosocial Rehabilitation, 2020)
Study habits are very essential for students to cultivate. They have to be nurtured and be given more time to attain success in life. However, good study habits should be coupled with appropriate time and place, and these could not be done without the willingness of the students. In today's generation of students, they learn in different ways. They use methods on how they could learn easily by assessing their capabilities, specifically, on what they could do or what they could not do based on their evaluation of their study habits. This research aimed to determine the significant relationship of study habits and learning preferences to the academic performance of second-year education students of First City Providential College. It used correlative methods and purposive sampling. Moreover, the quantitative method was employed in determining the profile of students, their academic performance, learning styles, study habits. Pearson's correlation coefficient was used as the statistical treatment to test the significant relationship between the given variables. The data were elicited from the responses of the respondents through the VARK Questionnaire (Version 8.01) and Palsane and Sharma Study Habits Inventory. Consequently, the results of the study led to the adoption of programs that will enhance the students’ preferred modalities and their study habits to achieve academic success.